Strategi Evaluasi dan Pengembangan Pendidikan Nilai pada PAI (Pendidikan Agama Islam) - Erick Yusuf; Sofyan Sauri (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This study aims to analyze strategies for the evaluation and development of value education in PAI. The method used is analytical description analysis with library research approach. Data is information obtained through books, magazines, newspapers and other literature that aims to form a theoretical basis. The results show that the evaluation and development of values education at PAI needs to be carried out so that the objectives of Islamic religious education can be achieved, namely to develop students who are faithful, devoted, and have noble character. For this reason, it is necessary in addition to consistency in the implementation of the concept but also research on the suitability of the implementation of the concept directly in the field so that cultural pluralism which more or less affects various elements of education can provide solutions in implementing national policies to the fullest. Keywords: evaluation strategy. value development. Islamic education